Pelatihan Asesor Akreditasi Instrumen Pendidikan Dasar Dan Menegah (DASMEN) Badan Akreditasi Nasiona - Ismayadi; Sri Handayani, Baiq; Arzani, M.; Satria Elmiana, Dewi (Institut Agama Islam Hamzanwadi Pancor, 2025)
In Permendikbudristek No. 38/2023 it is also stated that the National Accreditation Agency for Early Childhood Education, Basic Education, and Secondary Education, hereinafter referred to as BAN-PDM, is an agency that carries out accreditation of early childhood education units, basic education units, secondary education units, and equivalent education programs that in carrying out their duties are independent and professional. Thus, BAN-PDM assessors have the authority to accredit PAUD units and dasmen units. Assessors from dasmen also have the right to accredit PAUD units. The 2024 basic secondary instrument training for assessors is a professional development program specifically designed to improve the competence of assessors in using effective and relevant assessment instruments, ensuring that the assessment process carried out by assessors can produce accurate, relevant, and reliable data as a basis for decision making related to the quality of education. The expected results of the 2024 BAN-PDM Assessor Training activities include: 1. Having the ability to understand BAN-PDM accreditation policies and mechanisms. 2. Have the ability to understand changes in the mindset and culture of BAN-PDM assessors. 3. Understand the accreditation instruments that include the following components: Educator Performance in Managing Student-Centered Learning Processes, Leadership of the Head of Educational Units in Managing Educational Units, Learning Environment Climate, and Graduate and/or Student Learning Outcome Competencies. 4. Have the technical skills needed as an assessor. 5. Have the ability to use the Sispena application. 6. Understand integrity as an assessor.